Collective action and vulnerability: Burial societies in rural Ethiopia - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Collective action has intrinsic value. Being part of a group and participating in meeting common objectives provide direct benefits to individuals. In addition, collective action has an instrumental value; it can help individuals, groups, and communities achieve common goals. In Ethiopia, a study found that one form of collective action, iddir, or burial societies, helped households in the study areas attenuate the impact of illness.